Regulation of the Effect of Physical Activity Through MicroRNAs in Breast Cancer - Hong, Bok Sil (International Journal of Sports Medicine, 2021)
Physical activity and exercise can induce beneficial molecular and biological regulations that have been associated with an incidence of various diseases, including breast cancer. Recent studies demonstrated that the potential links between physical activity-induced circulating microRNAs (miRNAs) and cancer risk and progression. Here, we investigated whether altered miRNAs by exercise could influence breast cancer progression. After primary searching in PubMed and reviewing the full-text papers, candidate miRNAs altered by exercise in breast cancer were identified. Analysis of expression profiles and clinical outcomes of altered miRNAs using The Cancer Genome Atlas datasets showed altered miRNAs expressions were significantly associated with the patient's prognosis, whereas prognostic values of each miRNA varied in different stages and subtypes. In addition, altered miRNAs profiles regulated various target genes and key signaling pathways in tumorigenesis, including pathways in cancer and the PI3K-Akt signaling pathway; however, miRNAs regulated the expression of target genes differently according to tumor stages and subtypes. These results indicate that circulating miRNAs are promising noninvasive stable biomarkers for early detection, diagnosis, prognosis, and monitoring the response to clinical therapies of breast cancer. Moreover, stages and subtype-stratified approaches for breast cancer progression would be needed to evaluate the prognostic value of miRNAs for biomarkers and therapeutic targets.
Keywords: circulating miRNAs; exercise; biomarker; prognosis